The Influence of Marketing Mix and Service Quality on Customer Satisfaction and Its Impact on Customer Loyalty at PT Delta Primalab Saintifik - Delli Saptaji; Rudianto Rudianto; Khairul Anwar; FX Irwan Tanamas (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to analyze the influence of the marketing mix and service quality This study aims to analyze the influence of the marketing mix and service quality on customer satisfaction and its impact on customer loyalty at PT Delta Primalab Scientific. The marketing mix, which includes product, price, place, and promotion, is considered a crucial element in influencing customer satisfaction. In addition, service quality, which encompasses responsiveness, reliability, and empathy, also plays a significant role in building customer satisfaction and loyalty. This research employs a quantitative method using a survey technique (questionnaire) involving a sample of customers from PT Delta Primalab Scientific. The population of this study consists of 61 customers of PT Delta Primalab Scientific. The sampling technique used is the Slovin method, with a sample size of 53 respondents. Data analysis was conducted using SEM-PLS to determine the direct influence between the variables studied. The research results show that the marketing mix significantly influences customer loyalty (β₁ = 0.352, t = 3.747, p = 0.000). Service quality significantly affects customer loyalty (β₂ = 0.319, t = 2.478, p = 0.014). Customer satisfaction significantly impacts customer loyalty (β₃ = 0.320, t = 2.690, p = 0.007). The marketing mix significantly influences customer satisfaction (β₄ = 0.453, t = 3.799, p = 0.000), and service quality significantly influences customer satisfaction (β₅ = 0.445, t = 3.830, p = 0.000).